Effect of Ostomy Care Team Intervention on Patients With Ileal Conduit. Issue 5 (September 2019) - Zhou, Haiyan; Ye, Yufang; Qu, Haihong; Zhou, Huaxian; Gu, Shengyan; Wang, Tianhua
Abstract : PURPOSE: The purpose of this study was to investigate the effect of a nurse-led multicomponent intervention on ostomy-related complications, self-efficacy, and health-related quality of life in patients with an ileal conduit. DESIGN: Randomized controlled trial. SAMPLE AND SETTING: Forty-six patients who underwent radical cystectomy and creation of an ileal conduit participated in the trial; data were collected over a 6-month period. The study setting was Shanghai Pudong Hospital, affiliated with Fudan University, located in Shanghai, China. METHODS: Participants were randomly allocated to an experimental or control group. Participants in the control group received routine care over a 6-month period following ostomy surgery, while those in the experimental group received a nurse-led, multicomponent, structured intervention delivered by an ostomy care team. The Chinese language versions of the Stoma Self-Efficacy Scale (SSES) and the City of Hope Quality of Life-Ostomy (COHQOL-O) questionnaire were used to assess self-efficacy in stoma care and health-related quality of life. Ostomy-related complications including peristomal moisture-associated skin damage and uric acid crystal deposits in the peristomal area were also assessed. Fisher's exact test was used to compare the incidence of ostomy-related complications between the 2 groups. Independent-samples t tests were used to compare SSES and COHQOL-O scores. RESULTS: No statistically significant differences were found between demographic characteristics of the control and experimental groups. After 6 months, the incidence of complications was significantly lower in the experimental group as compared to the control group (4.35% vs 30.43%, P = .047). In addition, the mean SSES score was significantly higher in the experimental group (indicating greater self-efficacy in stoma care) (107.13 ± 11.87 vs 85.65 ± 12.87, P = .000), and the mean COHQOL-O score was also significantly higher in the experimental group, indicating higher health-related quality of life (154.48 ± 16.01 vs 138.26 ± 13.42, P = .001). CONCLUSION: The nurse-led multicomponent intervention provided by the ostomy care team reduced ostomy-related complications and improved the self-efficacy level and health-related quality of life in persons with a new urostomy.